An infrequent clinical case of mucosal fenestration: Treated with an interdisciplinary approach and regenerative therapy - Zeba Jafri; Nishat Sultan; Nafis Ahmad; Anika Daing (Wolters Kluwer Medknow Publications, 2019)
Mucosal fenestration is a clinical finding in which a portion of the tooth root is denuded of the overlying alveolar bone and gingiva or oral mucosa, thus exposing the root to the oral cavity. If left untreated, they may be a source of infection by giving entry to oral pathogen, leading to further progression of periodontal disease. Depending on their site of presence, they may also be a reason of esthetic concern to some patients. This paper reports one such infrequent case of mucosal fenestration of lower incisor region that was well treated by an interdisciplinary approach and regenerative therapy.